2005
DOI: 10.2135/cropsci2005.0486
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Management and Nitrogen Source Effects on Ultradwarf Bermudagrass Cultivars

Abstract: Increasingly, vegetative selections from ‘Tifdwarf’, ‘Tifgreen’, or other hybrid bermudagrass [Cynodon dactylon (L). Pers. × C. transvaalensis Burtt Davy] are slowly replacing Tifdwarf as the bermudagrass of choice for putting greens. The cultivars Champion, MS Supreme, TifEagle, and Floradwarf are examples of released ultradwarf bermudagrasses. The objective of this research was to evaluate these four cultivars, Tifdwarf, and an experimental ecotype (Mobile 9) for turf and overseed quality, color, shoot densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…This warm‐season species requires fewer fungicide and water inputs, as well as fewer in‐season labor inputs than creeping bentgrass ( Agrostis stolonifera L.) (4). However, the aggressive growth habit and high shoot density of ultradwarf bermudagrass can lead to excessive soil organic matter (SOM) accumulation (15).…”
Section: Characteristics Of Ultradwarf Bermudagrass Putting Greensmentioning
confidence: 99%
See 1 more Smart Citation
“…This warm‐season species requires fewer fungicide and water inputs, as well as fewer in‐season labor inputs than creeping bentgrass ( Agrostis stolonifera L.) (4). However, the aggressive growth habit and high shoot density of ultradwarf bermudagrass can lead to excessive soil organic matter (SOM) accumulation (15).…”
Section: Characteristics Of Ultradwarf Bermudagrass Putting Greensmentioning
confidence: 99%
“…Previous research on ultradwarf bermudagrass thatch management has focused on the effects of nitrogen source and cultivation techniques (15,29), but has not addressed the difficulty of incorporating sand topdressing into the turf canopy. The objective of this study was to compare three methods of incorporating sand topdressing following identical topdressing treatments into an ultradwarf bermudagrass putting green.…”
Section: Characteristics Of Ultradwarf Bermudagrass Putting Greensmentioning
confidence: 99%
“…Within 10 yr, patches of off‐type bermudagrass began to appear in Tifdwarf putting greens (Moncrief, 1975), and these patches were often phenotypically different from the original sprigged Tifdwarf (Caetano‐Anolles et al, 1995). Superior off‐types, with shorter internodes and higher shoot densities (Gray and White, 1999; Hollingsworth et al, 2005) were released as new cultivars. TifEagle, an irradiated mutant of Tifway II, is an example of a cultivar with such growth characteristics (Hanna and Elsner, 1999).…”
mentioning
confidence: 99%
“…A plausible reasoning for the observed differences in LSS and DSI among cultural management practices is the increased plant stress from mechanical wounding. Cultural management practices that cause mechanical injury to plant tissues decrease turf quality and expose turfgrasses to pathogen entry and infection (White and Dickens, 1984; Couch, 1995; Guertal et al, 2001; Hollingsworth et al, 2005; Uddin et al, 2008; Vines et al, 2017). Studies of UDB have indicated that increased frequency of cultural management practice application decreases turf quality and increases plant injury (White and Dickens, 1984; Guertal et al, 2001; Hollingsworth et al, 2005; Vines et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical injuries to plant tissues are associated with standard VM practices (Uddin et al, 2008). Such injuries render turfgrass plants vulnerable to entry and infection by pathogens and decrease turfgrass quality (White and Dickens, 1984; Guertal et al, 2001; Hollingsworth et al, 2005; Uddin et al, 2008; Vines et al, 2017). Park et al (2016) indicated that research is needed to determine the effects of other cultural management practices on UDB diseases.…”
mentioning
confidence: 99%